REL-1017 (esmethadone; d-methadone) does not cause reinforcing effect, physical dependence and withdrawal signs in Sprague Dawley rats - Jack Henningfield; David Gauvin; Francesco Bifari; Reginald Fant; Megan Shram; August Buchhalter; Judy Ashworth; Ryan Lanier; Marco Pappagallo; Charles Inturrisi; Franco Folli; Sergio Traversa; et al. (Scientific Reports, 2022)
Abstract REL-1017 (esmethadone, d-methadone) is the opioid-inactive d-isomer of racemic d,l-methadone. REL-1017 may exert antidepressant effects via uncompetitive N-methyl-d-aspartate receptor (NMDAR) channel block. As REL-1017 is expected to exert central nervous system activity, full characterization of its abuse potential is warranted. We evaluated lack of reinforcing effect, physical dependence, and withdrawal of REL-1017 in Sprague Dawley rats. (1) Self-administration Study Rats were trained to self-administer oxycodone intravenously (IV) and then were subjected to 3-day substitution tests where saline, oxycodone, and REL-1017 were self-delivered IV by a fixed number of lever presses; (2) Drug Discontinuation Study Rats were treated for 30 days by oral gavage with vehicle, REL-1017, ketamine or morphine and evaluated for withdrawal with functional observational batteries (FOBs). In the self-administration study, rats treated with saline, vehicle, and all REL-1017 doses showed the typical “extinction burst” pattern of response, characterized by an initial rapid increase of lever-pressing followed by a rapid decrease over 3 days. Rats treated with oxycodone maintained stable self-injection, as expected for reinforcing stimuli. In the withdrawal study, REL-1017 did not engender either morphine or ketamine withdrawal signs over 9 days following abrupt discontinuation of drug exposure. REL-1017 showed no evidence of abuse potential and did not engender withdrawal symptomatology.